Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru dan Mutu Sekolah - Muhammad Faqihudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
National Education aims to develop the potential of students to become human beings who believe and devote to Allah I, have noble, healthy, capable, creative, independent, intelligent and have a noble personality. To realize this the government and the community have tried to build education towards the desired joint, even though in reality the results of existing education are not yet satisfactory. The success of any educational institution is marked by In put - Process - Out put that is at the school. So schools that want high competitiveness will certainly pay attention to these three things, only then will the facilities and infrastructure that support them. The method used by the author in the research is with a qualitative approach, descriptive approach and field observation. From the results of the study, the authors conclude that the principal is the main key in realizing school to be competitive and competitive, although other factors also influence.